Porous polymer coatings as substrates for the formation of high-fidelity micropatterns by quill-like pens - Hirtz, Michael; Lyon, Marcus; Feng, Wenqian; Holmes, Andrea E.; Fuchs, Harald; Levkin, Pavel A. (Beilstein Journal of Nanotechnology, 2013)
We explored the potentials of microarray printing using quill-like microcantilevers onto solid supports that are typically used in microspot printing, including paper, polymeric nitrocellulose and nylon membranes. We compared these membranes with a novel porous poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate) support (HEMA) with narrow pore size distribution in the 150 nm range, which demonstrated advantages in pattern definition, spot homogeneity, and consistent spot delivery of different dyes (phloxine B and bromophenol blue) with diameters of several micrometres. The bromophenol blue arrays on HEMA support were used to detect the presence of bovine serum albumin (BSA). In the presence of BSA, the fluorescence spectrum observed from the bromophenol blue microarray exhibited a significant red shift of the maximum emission wavelength. Our results show that the porous HEMA substrates can improve the fidelity and quality of microarrays prepared by using the quill-like microcantilevers. The presented method sets the stage for further studies using chemical and biochemical recognition elements, along with colorimetric and fluorometric sensors that can be spotted by this method onto flat porous polymer substrates.
Keywords: microarrays; microscale printing; microspotting; polymeric porous support; polymethacrylate; quill-like pens